Effects of full transient Injection Rate and Initial Spray Trajectory Angle profiles on the CFD simulation of evaporating diesel sprays- comparison between singlehole and multi hole injectors. (15th January 2023) - Safiullah,; Chandra Ray, Samir; Nishida, Keiya; McDonell, Vincent; Ogata, Yoichi
Abstract: This paper investigates experimental and computational diesel sprays of single hole and multi hole injectors under vaporizing conditions. Two single hole and two ten-hole injectors with the same nozzle hole size are tested with the 120 MPa injection pressure. Experiments implement Laser Absorption Scattering technique. This method utilizes two wavelengths (Visible and Ultraviolet) of light and fuel's mixture concentrations are measured by attenuations of these lights. On the other hand, sprays are simulated in the Eulerian Langrangian two-phase fluid framework where KHRT and Multicomponent models are used as droplet breakup and evaporation models respectively. Full transient profiles of Injection Rate and Initial Spray Trajectory Angle are used as input boundary conditions for the spray simulation and effects on the spray characteristics are observed. Injection rates are measured with Bosch Long Tube and Initial Spray Trajectory Angles are extracted from the near nozzle field spray images. Experiments reveal that multi-hole injectors (0.101 mm and 0.133 mm) injectors depict longer liquid and shorter vapor penetrations. However, longer simulation liquid and vapor penetrations are seen for single hole injectors due to increased initial ramp-up phase. Sprays of Multi-hole injectors are diffused radially which promote air entrainment, better mixture formation, improved combustion, and lower exhaust emissions. Overall, simulated sprays using unfiltered injection rate profile as an input parameter showed an excellent agreement with experiments. While sprays using low-pass filtered injection rates showed a clear disagreement. Parameters including Liquid Length, Vapor Penetration and Evaporation ratios were found to be influenced by the IR profile rather than ISTA. Whereas vapor equivalence ratios depend on both input parameters plus breakup model constants. Highlights: Sprays of Multi hole diesel injectors show longer liquid and shorter vapor penetrations in experiments. Injection rates of Single hole injectors depict higher initial ramp-up phase, hence their simulation sprays are longer. Multi-hole injectors promote air entrainment and better mixture formation.